The Influence of Duolingo Application to EFL Classroom Students’ Motivation in Learning English - Fani Indrawan; Pipit Ertika Daristin; Elisa Nurul Laili (Journey: Journal of English Language and Pedagogy, 2023)
The advancement of technology have triggered the development of English language learning application. The massive use of smartphones is one of the factors in the emergence of the ELL application. This study aims to investigate the influence of Duolingo application to EFL students. This research is using quantitative method even though the data that had been collected from questionnaire, which used Likert Scale, were analyzed and interpreted using qualitative style. The results show that most of the students have positive sentiment towards the use of Duolingo as it is shown by the dominant prevalence of "Agree" and "Strongly agree" answers. However, in terms of competitiveness, Duolingo might not that convincing in making students have the desire to compete and get better score than their peers. Overall, students are aware with the motivational value that Duolingo potentially offers